DISCRIMINACIÓN LABORAL A NIVEL PROFESIONAL DE LA MUJER EN MÉXICO CASO: CIUDAD JUÁREZ EN LA MANUFACTURA - Urquidi, Adriana; Valencia, Nancy; Zarate, Vicente; Huerta, Christian (European Scientific Journal, ESJ, 2012)
The penetration of women in the workplace has led to many changes in attitudes and behavior patterns of social circles, economic and political, including the workplace, society and family.These changes have also been manifested in laws, especially in Mexican law that establishes the rights of women workers and which seeks gender equality, but the reality is that employment discrimination remains a problem today in Mexico. Despite the efforts of women to enter the labor market, their level of participation remains far below the male. Especially this gender inequality is more prominent leadership positions and decision-making in organizations.